5G Adoption and Usage in The General Public and SMEs – An Australian local council study - Jing GAO; Yuhui SUN; Ang YANG (Communications of International Proceedings, 2023)
Since the 5G commercial network was first launched by T-mobile US in 2018, 5G networks are rapidly expanding worldwide, transforming connectivity and communication. Since 2019, Australia has made significant investments in developing and deploying 5G technology. Australian businesses from various industry sectors, such as mining, manufacturing, and logistics, are leveraging the high-speed and low-latency capabilities of 5G to enhance productivity, optimise operations, and enable new innovations. While there are many studies on the 5G adoption in industry transformation, this research tries to investigate the general public and SMEs' perceptions towards 5G uptake by conducting a questionnaire survey and follow-up interviews. This research identifies the 5G network usage pattern of the general public and SMEs as well as the challenges in adopting the 5G network. The findings could enable a wide range of stakeholders, such as 5G application developers, infrastructure providers, and government policymakers, to provide customised services and enhance the quality of service provision.
Keywords: 5G adoption; SMEs; General Public and SMEs